2017
DOI: 10.3390/w9030179
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Recycled Water Quality and Clogging on Infiltration Rates at A Pioneering Soil Aquifer Treatment (SAT) Site in Alice Springs, Northern Territory (NT), Australia

Abstract: Infiltration techniques for managed aquifer recharge (MAR), such as soil aquifer treatment (SAT) can facilitate low-cost water recycling and supplement groundwater resources. However there are still challenges in sustaining adequate infiltration rates in the presence of lower permeability sediments, especially when wastewater containing suspended solids and nutrients is used to recharge the aquifer. To gain a better insight into reductions in infiltration rates during MAR, a field investigation was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Groundwater artificial recharge (GAR) has been considered worldwide as an extremely powerful candidate to address water reclamation and sustainable utilization, which increases water storage in aquifers directly to save water in periods of water surplus for use in periods of shortage in certain seasonally arid or semiarid regions (Beganskas & Fisher, ; Bouwer, ). However, clogging in infiltration porous media during recharge has been the bottle neck of GAR systems, resulting in a reduction in the infiltration rates and GAR performance levels (Barry, Vanderzalm, Miotlinski, & Dillon, ; Langhans et al, ; Pavelic et al, ; Skolasińska, ). Previous studies have even indicated that most GAR facilities encounter serious clogging problems within a very short operation period (Du, Wang, & Ye, ; Rinck‐Pfeiffer, Ragusa, Sztajnbok, & Vandevelde, ).…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater artificial recharge (GAR) has been considered worldwide as an extremely powerful candidate to address water reclamation and sustainable utilization, which increases water storage in aquifers directly to save water in periods of water surplus for use in periods of shortage in certain seasonally arid or semiarid regions (Beganskas & Fisher, ; Bouwer, ). However, clogging in infiltration porous media during recharge has been the bottle neck of GAR systems, resulting in a reduction in the infiltration rates and GAR performance levels (Barry, Vanderzalm, Miotlinski, & Dillon, ; Langhans et al, ; Pavelic et al, ; Skolasińska, ). Previous studies have even indicated that most GAR facilities encounter serious clogging problems within a very short operation period (Du, Wang, & Ye, ; Rinck‐Pfeiffer, Ragusa, Sztajnbok, & Vandevelde, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many coastal regions have adopted or will adopt management methods to improve fresh groundwater supply to compensate and control, for instance, the salinization of coastal aquifers (Oude Essink, ). In past decades, several techniques that might lead to an increase in freshwater availability have been investigated globally, such as Managed Aquifer Recharge (Bekele et al, ; Dillon, ; Dillon, Pavelic, Page, Beringen, & Ward, ; Page, Bekele, Vanderzalm, & Sidhu, ; Sprenger et al, ), Aquifer Storage and Recovery (Dillon et al, ; Page, Peeters, Vanderzalm, Barry, & Gonzalez, ), Soil Aquifer Treatment (Barry, Vanderzalm, Miotlinski, & Dillon, ; Fox et al, ; Sharma & Kennedy, ), and water desalination plants (El Saliby, Okour, Shon, Kandasamy, & Kim, ; March, Saurí, & Rico‐Amorós, ).…”
Section: Introductionmentioning
confidence: 99%
“…While surface water continues to be the main source water used in MAR (e.g., [7]), the use of other source water types such as desalinated seawater [2,19,20], treated waste water [20,21] and harvested rain water [5] and stormwater [22] is growing. Along with the variation of different source waters, the type and degree to which pretreatment is required to allow infiltration [22,23] are diverging as well.…”
Section: Source Water Types For Marmentioning
confidence: 99%
“…Along with the variation of different source waters, the type and degree to which pretreatment is required to allow infiltration [22,23] are diverging as well. Pretreatment, e.g., by coagulation, sand filtration or soil aquifer treatment (SAT), is needed to remove suspended fines from the source water, in order to prevent infiltration well clogging (e.g., [24]) and to maximize the recharge capacity during surface infiltration [21,24,25]. In addition, to limit the clogging risk by microbial growth, disinfection of the source water, e.g., using UV [21] or chemical pretreatment, e.g., to remove high organic matter contents [23], can be considered.…”
Section: Source Water Types For Marmentioning
confidence: 99%
See 1 more Smart Citation